Produtividade em pesquisa do CNPQ nas ciências químicas e geociências: perfil dos pesquisadores e critérios de julgamento - Cândido, Lucilene Faustina de Oliveira (2016)
The research productivity fellowship from CNPq is one of the most coveted scientific grants in Brazil. Although, it positively impacts the researcher's career and institution, the profile of this researchers is still unknown. This thesis presents the main bibliometric indicators related to the scientific judgment of PQ fellowships from the Coordination of the Research Program on Chemical Sciences and Geosciences (COCQG-CNPq). 1062 researchers from Chemistry and Geosciences had their profiles analyzed. The results from Chemistry and Geosciences show differences in the profiles of researchers from different subfields and specialties in the same main area, example H index in the specialties of chemistry and number of articles published in specialties of Geosciences. This results suggest that the bibliometric indicators analyzed in this study should be used with caution in the process of granting PQ fellowships since there are area, sub area and specialties specificities. This thesis to contribute to the scientific evaluation of researchers from exact sciences who long to become PQ fellows or to continue to be one of them. The study might also contribute to the improvement of the criteria established by the CNPq's Assessor Committees.